2007
DOI: 10.1080/02770900701209772
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology and Personality Factors Modify the Perception of Dyspnea in Asthmatics

Abstract: We studied the relationship between the intensity of dyspnea and psychopathological and personality dimensions in 74 women and 38 men (mean age 49.7 years) with asthma. The women had higher values for the following variables: depression, anxiety-trait, and neuroticism, and they proved to have a greater external control location than the men. After checking the spirometry results, body mass index (BMI) and gender, it was found that dyspnea correlated with anxiety-trait and anxiety-state, neuroticism, and depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 21 publications
(16 reference statements)
0
14
0
1
Order By: Relevance
“…NOWOBILSKI et al [65] reported that dyspnoea correlated with anxiety trait and anxiety state, neuroticism, and depression in asthmatic males but not in females. Furthermore, KATON et al [66] observed that youths with asthma have an almost two-fold higher prevalence of comorbid anxiety and depressive disorders compared with controls.…”
Section: Psychopathologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…NOWOBILSKI et al [65] reported that dyspnoea correlated with anxiety trait and anxiety state, neuroticism, and depression in asthmatic males but not in females. Furthermore, KATON et al [66] observed that youths with asthma have an almost two-fold higher prevalence of comorbid anxiety and depressive disorders compared with controls.…”
Section: Psychopathologiesmentioning
confidence: 99%
“…Psychological factors may trigger asthma symptoms and affect patients' asthma symptom perception, but also may influence medication compliance and, thus, should be detected and treated promptly and appropriately [62][63][64][65][66]. These conditions are associated with an increased use of urgent care and hospital admissions [67,68].…”
Section: Psychopathologiesmentioning
confidence: 99%
“…Psychological conditions may affect asthma in modulating symptoms' report or perception, or in influencing medication compliance and follow-up, disease assessment and self-monitoring and they are associated with more frequent urgent care and hospitalizations [124][125][126][127]. Dyspnea correlates with anxietytrait and anxiety-state, neuroticism and depression in asthmatic men [128]. Katon et al observed that youths with asthma have an almost twofold higher prevalence of comorbid anxiety and depressive disorders compared with controls [129].…”
Section: Psychopathologiesmentioning
confidence: 99%
“…Comparable results were found in COPD subjects with and without panic attacks ( Livermore et al, 2008 ; Giardino et al, 2010) . In asthma, the perception of dyspnea is worse with more severe inflammation, older age, depression ( Foschino-Barbaro et al, 2010 ), and anxiety-trait ( Nowobilski et al, 2007) . These findings suggest that mechanism(s) of dyspnea in parenchymal lung diseases differ from CFS.…”
Section: Discussionmentioning
confidence: 99%